The Rape of Lucretia, premier « opéra anglais » de Britten ? - Gilles Couderc (Revue LISA)
The Rape of Lucretia is Britten’s second opera, composed in the wake of the popular success of Peter Grimes and amidst the composer’s difficulties in sustaining his ambitious project to restore English opera and to set up his own opera company despite the dire post-war economic context. As Britten’s first chamber opera and the only one that retells a story from Roman Antiquity it stands apart in the Britten canon. But the collaboration of designer John Piper for the scenery and of Ronald Duncan for the libretto, the resort to dramatic verse, the borrowings from Blake, Donne and Shakespeare, as well as the musical references to English oratorio and Purcell and to Britten’s own personal questioning contribute to making it Britten’s first “English opera”.